Patient’s Satisfaction towards the Behavior of the Hospital Staffs - Bashyal, Sukriti; Ghimire, Ananda (International Journal of Atharva, 2024)
The study investigates the punctuality and behavior of hospital staff and examines the relationship between socio-demographic characteristics and these factors among patients in Kathmandu hospitals. Data was collected from 128 participants through structured questionnaires and their aged were above 20 years of age. Descriptive analysis shows that a majority are female, unmarried, and with a high school education. The findings indicated that most patients perceived the hospital staff, including registration, lab, blood bank, and nursing staff, as punctual and polite. Majority respondents realized improvements in their health compared to post-visit. Correlation analysis showed no significant relationships between gender and satisfaction, or between the number of hospital visits and satisfaction levels. These results highlight the generally positive perceptions of hospital services.